Recent Advances of Spectrometric and Spectroscopic Techniques in Food Quality and Safety - Lu, Weiying; Chen, Yanping (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Today, spectrometric and spectroscopic techniques are the gold standard for studying food quality and safety. They are ideal and versatile tools in the evaluation of functional components, such as proteins and lipids, as well as key components related to food safety, such as pesticide residues, pollutants, authentication, and illicit adulterants. Spectrometry and spectroscopy are also the cornerstone of many modern biochemical techniques, such as proteomics and metabolomics. This Special Issue, entitled "Recent Advances of Spectrometric and Spectroscopic Techniques in Food Quality and Safety" introduced explorations and advancements in food quality and safety and prospects for future application trends related to spectrometry and spectroscopy.